PENGARUH KOMPENSASI, PELATIHAN, DAN PENGEMBANGAN TERHADAP KINERJA PEGAWAI DI BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) KABUPATEN KARO - MENANTI SEMBIRING; ESRA TARIGAN; NEVIA YANTI (JURNAL ILMIAH KOHESI, 2021)
This research aims to test the influence of compensation, training, and development to employee’s performance at BadanPenanggulangan Bencana Daerah (BPBD) Kabupaten Karo, with partial or simultan. The sampling technique used wassaturated sampling technique with total sample of 63 peoples. This research uses descriptive research with a quantitativeapproach. Analysis of data used multiple linear regression analysis. The results showed that compensation, training anddevelopment together had a positive effect to employee’s performance, this is indicated by F test, F count > F table (350,829> 2,76) with a significance level of 0.000 <0.05. Compensation has a positive and significant effect to employee’sperformance, this is indicated by t count 8.913> t table 2.001 and a significance value (Sig.) 0.000 <0.05. Training has apositive and significant effect to employee’s performance, this is indicated by t count 4.677> t table 2.001 and a significancevalue (Sig.) 0.000 <0.05. Development has a positive and significant effect to employee’s performance, this is indicated by tcount 2.018> t table 2.001 significance value (Sig.) 0.048 <0.05. The results also show that compensation, training, anddevelopment have an effect to employee’s performance by 94.4% while the remaining 5.6% is affected by other variableswith coefficient of determinacy test (R2).